Mycobacterium smegmatis recombinante expressando a proteína CMX induz resposta imune contra Mycobacterium tuberculosis em camundongos BALB/c - Oliveira, Fábio Muniz de (2014)
For hundreds years tuberculosis (TB), a contagious disease caused by Mycobacterium tuberculosis (Mtb), has been a global public health problem. Even after the development of the vaccine BCG, in 1921, tuberculosis control continues on slow pace. This comes to be as a result of the variable efficacy (from 0 to 80%) presented by the vaccine in the protection against TB in adults. Therefore, the development of a new vaccine against TB is necessary. In this study, it was evaluated a recombinant vaccine composed of Mycobacterium smegmatis expressing the CMX fusion protein (mc2- CMX), formed from three antigen epitopes of Mtb: Ag85C, MPT51 and HspX. M. smegmatis mc2 155 was transformed with pLA71-CMX by electroporation, and the presence of the CMX protein was confirmed by imuno blotting. BALB/c mice were distributed in four groups: saline, infection, BCG and mc2-CMX. The groups were immunized with their respective vaccines in two moments with an interval of fifteen days and the animal blood was collected fifteen days after the last immunization. Thirty days after the last immunization, the animals were challenged with Mtb H37Rv (intravenously) and thirty days after the challenge, the blood was collected to perform ELISA test. Seventy days after the challenge, the lungs from all mice were collected to obtain cells for flow-cytometry, histological analysis and also to determine the bacillary burden. The immunization with mc2-CMX induced higher levels of antibodies of IgG1 (1,910±0,70) and IgG2a (0,139±0,020) class anti-CMX when compared with BCG group (0,646±0,19 and 0,413±0,24; respectively, p<0,05). These results demonstrated the relevance of CMX antigen in the immunogenicity of the recombinant vaccine. Seventy days after the challenge, the amount of T CD4 cells in the lung producing Th1- type cytokines was assessed. It was observed a significant increase in the percentage of T CD4 cells positive for IFN-γ and TNF-α in the immunized mice with mc2-CMX vaccine, when compared with the group immunized with BCG. Mice challenged with Mtb presented significant higher percentage of IL-2 producer cells when compared with the non-immunized group. However, only the mice immunized with the vaccine mc2- CMX presented significant higher percentage when compared with the infection group. The immune response induced by the vaccine was effective in the control of Mtb infection, confirmed by the histological analysis and the bacillar burden determined. The groups vaccinated with mc2-CMX and BCG presented a significant reduction of the lung lesion induced by the Mtb infection, and also lung bacterial load, when compared with the infection group. Thus, the recombinant vaccine mc2-CMX presents potential characteristics to be used in the prevention of TB.